Implementasi Manajemen Wakaf Tunai (Studi pada badan Ziswaf Kopontren Al-Yasini Pasuruan) - M. Rif'an Syadali (ITB AAS INDONESIA Surakarta, 2023)
Waqf is one of the instruments in the Islamic economy that aims to achieve goals in the Islamic economy, namely creating a prosperous life. Waqf is still considered as a practice for rich people, because waqf payments are synonymous with land and buildings. Therefore, currently in Indonesia a new alternative regarding waqf payments has emerged, namely cash waqf with the emergence of Law no. 41 of 2004 concerning the management of cash waqf funds. This study will describe the implementation of cash waqf in Al-Yasini Kopontren Ziswaf Agency as an Amil Zakat Institution that has implemented cash waqf. This study uses a qualitative approach with data analysis methods using interactive models. From the results of this study it is known that the implementation of cash waqf funds in the Al-Yasini Kopontren Ziswaf Board is invested in the form of shares in the retail business